Effect of Silica Fume on the Hydration Kinetics of Atbra Cement Pastes Produced in Sudan (Thamar University Journal of Natural & Applied Sciences, 2023)
Blended cement pastes were prepared with and without super plasticizer using an initial water/cement ratio of 0.30. Hydration kinetics were followed by determining the non-evaporable water and free lime contents at various hydration times, covering the range from 0.5 hour up to 28 days. The results of hydration kinetics indicated three-stages in the hydration reaction; these are the "dormant", the "accelerations" and the diffusion periods. In this study, Atbra Portland cement pastes were prepared with Silica fume as an admixture. This work is aimed to evaluate the effect of Silica fume on the effect of this admixture on the hydration reaction of cement pastes at different intervals of time (0.5 hours up to 28days).